Latvia - Beyond territorial reform - World Bank (Washington, DC, 2013)
The large number of local governments in a sparsely populated country such as Latvia, calls for the consolidation of these local governments, which is what the Government is now attempting to implement. This will require reforms to achieve improvements in local services, to change the basis for financing teachers' salaries, or to rationalize the allocation of hospital funding, among many others. Additionally, to meet the European Union standards for solid waste management, water supply, sanitation, and wastewater treatment, the Government will have to establish inter-municipal, or regional institutions to meet operational requirements, as well as a regulatory framework that increases water tariffs and improves operations. In financing social assistance, the Government may need to further finance areas where poverty incidence is unusually high. The report also addresses the new changes in the organization, and functions of intermediate levels of government, suggesting the Government could consider assigning functions, such as the organization of public transport, the management of roads funds, or other public services, to a larger unit of sub-national government. The five recently created planning regions, might be an appropriate basis for such level of government.